Orientation of Tribolium castaneum (Coleoptera: Tenebrionidae) adults to 4, 8-dimethyldecanal, kairomone and botanical oils following ambient, low, or high temperature exposure. (December 2021) - Bandara, H.M.D.S.; Wijayaratne, L.K.W.; Egodawatta, W.C.P.; Morrison, W.R.
Abstract: The aggregation pheromone 4, 8-dimethyldecanal (4, 8 DMD) used alone or with kairomone-baited traps generally is used for monitoring Tribolium castaneum (Herbst) but low efficiency is reported. Furthermore, insect orientation to pheromones and kairomones following low or high temperature exposure is not yet understood. This research evaluated the orientation of T. castaneum adults to 4, 8 DMD and common kairomones following exposure to ambient, low or high temperatures. Fifty adults were introduced to the middle of rectangular glass chamber, and movement to the treatment or control was determined after 1 h. In experiment 1, insects reared at 30°C were used. Experiments 2 and 3 used insects exposed to 10°C for 4 days (cold temperature) and 42°C for 12 h (brief high temperature), respectively at 2–8 h following cold or heat exposure. The highest trapping occurred when 4, 8DMD was combined with neem oil whereas the lowest was in coconut oil alone. Neem oil alone demonstrated repellent action. Prior exposure to cold or heat initially reduced taxis of T. castaneum adults to traps. The attraction for adults exposed to cold and heat was restored after 6–8 h when traps contained pheromone + neem or coconut oil. This study marks the first to experimentally test how exposure to high or low temperatures, two key IPM tactics in the post-harvest supply chain, affects the behavioral response of an important stored-product species to pheromone- and kairomones-baited traps. Highlights: 4, 8-DMD with kairomones, coconut oil or neem oil enhanced T. castaneum trapping. Pre-exposure to high or low temperature affects orientation of T. castaneum adults. High/low temperature increased T. castaneum adults trapped after initial decrease.